Evaluation of Performance Indicators and Frequency of Patient Referrals in the Hospitals Affiliated to Babol University of Medical Sciences in 2013 - AA Moghadamnia; MA Jahani; A Bijani; M Yaminfirooz; A Naghshineh; K Mohammadnia (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2016)
BACKGROUND AND OBJECTIVE: Performance indicators are important tools for the planning, organization, and coordination of hospital services in geographical regions and utilization of medical facilities within the covered populations. This study aimed to evaluate performance indicators and frequency of patient referrals in the hospitals affiliated to Babol University of Medical Sciences, Iran in 2013.